STUDI KERAGAMAN MORFOLOGI AKSESI PISANG KOLEKSI DARI KABUPATEN LAMPUNG SELATAN - Sobir Sobir; Cynthia Rozyandra; Kusuma Darma (Floribunda, 2006)
Sobir, Cynthia Rozyandra & Kusuma Darma. 2006. Morphological varibility of collection Banana in South of Lampung resident. Floribunda 3(1): 19-27. --- Lampung was famous as main production of banana in Indonesia, particularly in South of Lampung regency. In order to ellucidate the genetic basis of banana, it was collected 21 banana germplasms from Lampung Selatan and grown in Pasir Kuda Research Station of Center for Tropical Fruit Studies. The potential of the germplasm was elucidate through phenotipyc variability analysis by employing 41 morphological characters. Dendrogram generated using SAHN-UPGMA (Sequential, Agglomerative, Hierarchical, and Nested-Unweighted Pair-Group Method, Arithmetic-average) indicated that the evaluated accessions separated at 0.56 coefficient of dissimilarity, subsequently at 0.45 level coefficient of dissimilarity, the accessions divided into five primary groups. A Principal Component Analysis resulted that 81.0120% of genetic variability successfully revealed by ten principles components, score plot based on first and second principle component described 61.26% of variability and split the accessions into six primary groups. These result indicated that grouping pattern of both analysis not equal, this was probably because of 41 component simplified into two component that described lower than 70% of variability. However, the grouping has been successfully revealed the putative genome type of the collected banana accesions.